Pentafluoropyridine functionalized novel heteroatom-doped with hierarchical porous 3D cross-linked graphene for supercapacitor applications. Issue 43 (6th August 2021) - Kumar, Amit; Tan, Chih-Shan; Kumar, Nagesh; Singh, Pragya; Sharma, Yogesh; Leu, Jihperng; Huang, E.-Wen; Winie, Tan; Wei, Kung-Hwa; Tseng, Tseung Yuen
Abstract : Demonstration of the effect of Gibbs free energy ( G T = −643.26 eV) on N, P, F co-doped graphene, simulated via density functional theory (DFT). Abstract : The fabrication with high energy density and superior electrical/electrochemical properties of hierarchical porous 3D cross-linked graphene-based supercapacitors is one of the most urgent challenges for developing high-power energy supplies. We facilely synthesized a simple, eco-friendly, cost-effective heteroatoms (nitrogen, phosphorus, and fluorine) co-doped graphene oxide (NPFG) reduced by hydrothermal functionalization and freeze-drying approach with high specific surface areas and hierarchical pore structures. The effect of different heteroatoms doping on the energy storage performance of the synthesized reduced graphene oxide is investigated extensively. The electrochemical analysis performed in a three-electrode system via cyclic voltammetry (CV), galvanostatic charging–discharging (GCD), and electrochemical impedance spectroscopy (EIS) demonstrates that the nitrogen, phosphorous, and fluorine co-doped graphene (NPFG-0.3) synthesized with the optimum amount of pentafluoropyridine and phytic acid (PA) exhibits a notably enhanced specific capacitance (319 F g −1 at 0.5 A g −1 ), good rate capability, short relaxation time constant ( τ = 28.4 ms), and higher diffusion coefficient of electrolytic cations (Dk + = 8.8261 × 10 −9 cm 2 s −1 ) in 6 M KOH aqueous electrolyte. The density functional theory (DFT) calculation result indicates that the N, F, and P atomic replacement within the rGO model could increase the energy value ( G T ) from −673.79 eV to −643.26 eV, demonstrating how the atomic level energy could improve the electrochemical reactivity with the electrolyte. The improved performance of NPFG-0.3 over NFG, PG, and pure rGO is mainly ascribed to the fast-kinetic process owing to the well-balanced electron/ion transport phenomenon. A symmetric coin cell supercapacitor device fabricated using NPFG-0.3 as the anode and cathode material with 6 M KOH aqueous electrolyte exhibits maximum specific energy of 38 W h kg −1, a maximum specific power of 716 W kg −1, and ∼88.2% capacitance retention after 10 000 cycles. The facile synthesis approach and promising electrochemical results suggest this synthesized NPFG-0.3 material has high potential for future supercapacitor application.